Optical and structural characterisation of epitaxial nanoporous GaN grown by CVD. (21st August 2017) - Mena, Josué; Carvajal, Joan J; Martínez, Oscar; Jiménez, Juan; Zubialevich, Vitaly Z; Parbrook, Peter J; Diaz, Francesc; Aguiló, Magdalena
Abstract: In this paper we study the optical properties of nanoporous gallium nitride (GaN) epitaxial layers grown by chemical vapour deposition on non-porous GaN substrates, using photoluminescence, cathodoluminescence, and resonant Raman scattering, and correlate them with the structural characteristic of these films. We pay special attention to the analysis of the residual strain of the layers and the influence of the porosity in the light extraction. The nanoporous GaN epitaxial layers are under tensile strain, although the strain is progressively reduced as the deposition time and the thickness of the porous layer increases, becoming nearly strain free for a thickness of 1.7 μ m. The analysis of the experimental data point to the existence of vacancy complexes as the main source of the tensile strain.